Etiological diagnosis reduces the use of antibiotics in infants with bronchiolitis (Clinics, 2012)
OBJECTIVE: Acute bronchiolitis is a leading cause of infant hospitalization and is most commonly caused by respiratory syncytial virus. Etiological tests are not required for its diagnosis, but the influence of viral screening on the therapeutic approach for acute bronchiolitis remains unclear. METHODS: A historical cohort was performed to assess the impact of viral screening on drug prescriptions. The study included infants up to one year of age who were hospitalized for bronchiolitis. Virus screening was performed using immunofluorescence assays in nasopharyngeal aspirates. The clinical data were obtained from the patients' medical records. Therapeutic changes were considered to be associated with viral screening when made within 24 hours of the release of the results. RESULTS: The frequency of prescriptions for beta agonists, corticosteroids and antibiotics was high at the time of admission and was similar among the 230 patients. The diagnosis of pneumonia and otitis was associated with the introduction of antibiotics but did not influence antibiotics maintenance after the results of the virus screening were obtained. Changes in the prescriptions were more frequent for the respiratory syncytial virus patients compared to patients who had negative viral screening results (p =0.004), especially the discontinuation of antibiotics (p